What do small cetaceans tell us about trace elements pollution on the Argentinean coast? Franciscana dolphin as a biomonitor - Polizzi, Paula Sabrina; Romero, María Belén; Chiodi Boudet, Leila Natalia; Dolagaratz Carricavur, Arantxa; Gerpe, Marcela Silvia (Science of The Total Environment)
Trace elements (TEs) constitute the oldest emerging pollutants globally, most occur from natural sources, but a few are derived from anthropogenic sources. Marine mammals are considered bioindicators of ecosystem contamination. The aims of this review is compile reports on essential and nonessential TEs occurrence in small cetaceans from Argentinean waters; and to review the existing information on the concentration of TEs in the Franciscana dolphin, a biomonitor species of the Argentine coastal marine ecosystem. We searched reports where levels of TEs were present in small cetaceans from and eight species were analysed: Pontoporia blainvillei, Tursiops truncatus gephyreus, Kogia breviceps, Delphinus delphis, Lagenorhynchus obscurus, Lagenodelphis hasei, Cephaloryhchus commersonii and Ziphius cavirostris. Essential TEs like Zn, Cu, Mn, Cr, Fe, Co, Ni, Mo, Se, As, Au, Ag, Sn, and nonessential TE as Pb, Cd, Hg, As was considered. The reports compiled in this article analysed kidney, liver, muscle and occasionally brain, skin, lung and spleen, covering a temporal range of 30 years, from 1982 to 2016. Of data analysis, we identify knowledge gaps, species of small cetaceans for which the concentration of trace metals is not yet known and areas on the Argentine coast where there are no reports that analyse them. The most recent information corresponds to the 2010 decade, and in those subsequent publications, the samples were taken at that time. This emphasizes the importance of reviewing this data, in order to compare old and new datasets, create contamination timelines and evaluate possible increases or decreases of contaminants in different study areas. The information recopilated will serve as valuable baselines to detect the future impact of increasing human, even natural, activities on marine ecosystems in the South Atlantic Ocean. Fil: Polizzi, Paula Sabrina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y ...